Identifikasi Kebutuhan Fasilitas Bank Sampah untuk Menunjang Kesehatan Lingkungan dan Kewirausahaan - Sedayu, Agung (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Waste problems are common in almost all regions in Indonesia. Starting from overloaded capacity of waste disposal sites, inadequate waste sorting, limited availability of officers and waste transport, and low public awareness to be wiser in managing their own waste. Action is needed that can facilitate and speed up the resolution of the waste problem. Currently, the waste bank solution is one of the easy and simple methods used by every region in Indonesia. Almost every region in Indonesia has centralized waste bank facilities and sub-waste banks spread across certain points which have been arranged and planned on a scheduled basis to collect and distribute waste. This article aims to identify the need for waste bank processing facilities in the Velodrome area, Madyopuro sub-district, Kedungkandang District, Malang City, East Java. This identification was carried out by means of a field survey and compared to standard references for waste bank facilities. It is hoped that a waste bank processing site with complete facilities can support environmental cleanliness and health, and also to create creativity to support the social entrepreneurship.